Women Empowerment in Disaster Vulnerable Village Through Vocational Life Skill Education Based on Utilization of Local Potential - Tohani, Entoh; Prasetyo, Iis; Suharta, RB. (Journal of Nonformal Education, 2019)
Woman empowerment is one important and appropiate action to the area because there is rarely education which focus on build productive skills of woman to using local wisdom to be more useful. This research aims to develop women competence in disaster vulnerable village to understand and manage a local wisdom through vocational life skills education in context of increasing quality of the family and community socio-economy. The research is action research which has steps include issue analyzing, planning, implementation, and evaluation of action. The action is vocational life skills education. Its research subjects are 25 women in Sengir Village, Kalirejo, Kokap, Yogyakarta as target group. They chosen by the local government consideration and the group characteristic such as wifes of people producing coconut essence, who are till productive and motive to develop. Data collected by interview, observation, and questionnair and analyzed by qualitative analysis techniques. The data validity obtained by perseverance of observation, triangulation, and expert validation. The results of study reveal that the target group was able to develop awareness of utilization of the local potential, having attitudes, knowledge and skills of its production, and creating of the joint business. The existence of women's empowerment makes it more productive in economic activities in order to achieve their welfare.